Physicians' Exercise Habits: Most believe in exercise but don't do enough - Stevenson, Lisa M. (1992)
We distributed a questionnaire on personal exercise profiles, attitudes toward exercise, and counseling behavior to a random sample of 200 Vancouver general practitioners. Of the respondents, 39.1% met American College of Sports Medicine guidelines. Personal attitudes influenced counseling practices. Physicians believed that exercise was important and were prepared to counsel, but considered themselves only somewhat successful at changing patients' behavior.